Prevalence of entrepreneurial management practices in technology-based firms - Abdul Majid, Izaidin; Dora, Mohd Taib; Md Saad, Mohd Shamsuri; Ismail, Kamariah (2008)
It has been widely agreed that entrepreneurship leads to firms' success. Since companies with a high level of entrepreneurial propensity are focussed on "the pursuit of opportunity regardless of resources currently controlled", it can be expected that those companies will be highly leveraged, resulting in high performance and effectiveness and eventually will lead to business success. Stevenson's six dimensional construct of Entrepreneurial Management (EM), as interpreted and operationalised by Brown et al. (2001), consists of strategic orientation (SO), resource orientation (RO), management structure (MS), reward philosophy (RP), growth orientation (GO) and entrepreneurial culture (EC). This study attempts to explore on the issue of as to what extent the entrepreneurial management approach is being adopted by the sample firms. Based on the global measure of EM, the results of the descriptive statistical analysis suggest that a large majority of the firms may be classified as entrepreneurial. On further investigation on each dimension of the EM construct, mixed results were found on the prevalence of EM. MS, SO and EC dimensions show high prevalence in firms with strong entrepreneurial propensity. This indicates that the firms tend to be more entrepreneurial with regard to the MS, SO and EC dimensions. However, for the GO and RO dimensions, the results show that the sample firms tend to be on the average scores.